INFLUENCE OF COMPANY SIZE, DIVIDEND POLICY, CAPITAL STRUCTURE AND PROFITABILITY TO EARNINGS RESPONSE COEFFICIENT - Maya Sabirina Panggabean; Eloi H. Situmorang; Lestaria Posmauli Silitonga; Yosefa Turnip (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2022)
The purpose of the study is to see how the influence of company size, dividend policy, capital structure and profitability on the manufacturing sector's Earnings Response Coefficient recorded on the IDX for the 2017-2020 period. Data information is obtained from financial reports listed on the IDX. Quantitative method is determined to be the method for this research by utilizing secondary data. A total of 172 companies were made into the population and with purposive sampling technique, a sample of 132 companies was obtained from 33 companies. ERC is used as the dependent variable and firm size, dividend policy, capital structure, profitability are used as independent variables. Based on the research, it can be concluded that (1) the size of the company has a negative and insignificant effect on the Earnings Response Coefficient. (2) Dividend policy has a positive and significant effect on the Earnings Response Coefficient. (3) Capital structure has no and no significant effect on the Earnings Response Coefficient. (4) Profitability has no and no significant effect on the Earnings Response Coefficient. With the results of Adjusted R Square 47.1% of the ERC and the remaining 72.1% influenced by other variables. So the overall results of Company Size, Dividend Policy, Capital Structure, Profitability simultaneously have no effect on the Earnings Response Coefficient in the Manufacturing sector contained in the Indonesia Stock Exchange.